Achieving Sustained, Indigenous and Inclusive Growth (The Allama Iqbal Lecture) (The Pakistan Development Review, 2016)
The world economy is now facing paramount problems such as long tern stagnation of economic growth and worsening income distributions (or economic polarisation). This is even more embarrassing, because the humans have been seeking more equal society during the post-WWII era by engaging in the revised capitalism or social democracy by the most of capitalist developed economies, the balanced growth strategies under social democracy by most of the developing economies and more dramatically the socialist economic regime by the already collapsed socialist blocs, not to mention the still barely surviving North Korea. “Growth stagnation and economic polarisation” is not the one which has been intended and anticipated by policies but is opposite to intention as well as expectations. Some of the critics on capitalist economy have been arguing that this is the outcome of the fundamental contradiction of the capitalist economy from the Marxian perspective and/or the result of the neoliberal policies since the 1980s [Piketty (2014) and Stiglitz (2012)]. However, if one understands that the neoliberalism had short-lived only during the Thatcher-Reagan era, of course with some lingering effects, this episode can be seen as a typhoon within the tea cup. In this regard, broadly speaking, the common underlying institutions of post-war politicaleconomy regime of the world economy can properly be called as the economic equalityseeking “egalitarian democracy” which includes the revised capitalism and social democracy, not to mention the socialism. Therefore, one can see that the efforts to create more economically equal society or in other words, the shared growth have in fact created more unequal as well as growth-stagnated economies against the intention as well as expectation. This seems to be the fundamental dilemma faced now by the world economies and these are perhaps waiting for the economic as well as any other social science profession to come up with a solution to it. Of course, some naive Marxists or leftist economists would claim that this phenomenon of the worsening income inequality is simply the fact of the capitalist economy